Перспективи розвитку підприємництва у сучасних умовах господарювання - Kobelia, Zoriana; Todoruk, Sergy (My University, 2023)
У статті розглянуто вплив пандемії COVID-19 та збройного нападу й повномасштабного вторгнення на стан та перспективи розвитку підприємництва в Україні. Досліджено проблеми, розроблено можливі заходи подолання впливу негативних наслідків воєнних дій в Україні на розвиток малого та середнього підприємництва. Здійснено аналіз результатів дослідження українського бізнесу під час воєнного стану, що проведене центром розвитку інновацій, національний проєкт Дія.Бізнес, Офісом з розвитку підприємництва та експорту спільно з Advanter Group за підтримки Європейського Союзу в межах Ініціативи для відновлення економіки, розвитку підприємництва й експорту України. Визначено найбільш популярні сфери діяльності малого та середнього бізнесу в Україні, досліджено проблеми та потреби суб’єктів підприємництва в залежності від географії їх діяльності. Окреслено основні перешкоди в розвитку бізнесу. Запропоновано основні рішення бізнесу на 2022-2023 рік.
PROSPECTS FOR THE DEVELOPMENT OF ENTREPRENEURSHIP IN MODERN ECONOMIC CONDITIONS
The article examines the impact of the COVID-19 pandemic and the armed attack and full-scale invasion on the state and prospects for the development of entrepreneurship in Ukraine. The problems were studied, and possible measures were developed to overcome the impact of the negative consequences of military actions in Ukraine on the development of small and medium-sized enterprises. An analysis of the results of the study of the state of Ukrainian business during martial law, conducted by the Center for the Development of Innovations, the national project Diya.Business, the Office for the Development of Entrepreneurship and Export, together with Advanter Group, with the support of the European Union, was carried out within the Initiative for the recovery of the economy, development of entrepreneurship and export of Ukraine. It was determined that the civilized development of small business is possible only in the presence of a long-term development strategy focused on economic, social, informational, educational and other types of small business support. Small businesses are most prone to crises and negative consequences of changes, and in Ukraine, due to the ongoing war, these factors naturally have a negative impact on the development of small businesses. In the specified conditions, the absolute and relative growth of small business in Ukraine, against the background of the general decline in production and the crisis state of many large enterprises, including monopolies, demonstrates its great internal potential, the opportunity for fairly broad sections of the population to ensure their economic independence and well-being on their own, similar to how it happens in EU countries. In order to support business, the Government introduced changes in regulatory and tax policy, provides financial support to business, implements relocation programs and supports its export potential. International programs for the development of entrepreneurship introduce numerous training programs to support entrepreneurs and allocate grants for entrepreneurial activity. The most popular areas of activity of small and medium-sized businesses in Ukraine were determined, the problems and needs of business entities were investigated depending on the geography of their activity. The main obstacles in business development are outlined. The main business solutions for 2022-2023 are proposed.
Keywords: підприємництво; розвиток підприємництва; воєнний стан; програми державної підтримки; малий та середній бізнес; entrepreneurship; development of entrepreneurship; martial law; state support programs; small and medium business